2000
DOI: 10.4049/jimmunol.165.4.2028
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Monocytes to Macrophages Switches theMycobacterium tuberculosisEffect on HIV-1 Replication from Stimulation to Inhibition: Modulation of Interferon Response and CCAAT/Enhancer Binding Protein β Expression

Abstract: HIV-1 replication is inhibited in uninflamed lung macrophages and is stimulated during tuberculosis. Attempts to recapitulate activation of HIV-1 replication in primary monocytes and macrophages ex vivo and in the untreated and PMA-treated THP-1 cell line model in vitro have produced opposite results depending on the state of differentiation of the cells. After infection with Mycobacterium tuberculosis, monocytes enhanced HIV-1 replication and produced a stimulatory 37-kDa CCAAT/enhancer binding protein β (C/E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
118
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(130 citation statements)
references
References 73 publications
9
118
0
Order By: Relevance
“…Our results about IFN-␣ production from Mtb-infected MDDC are consistent with the data of Cella et al, who found plasmacytoid DC produce type I IFN in mycobacteria-infected lymph nodes (50). It has been also shown that Mtb infection leads to secretion of type I IFN from THP-1 cells (48). All together these observations indicate that the production of IFN type I could play a dual role in Mtb infection by promoting both Th1 and DC differentiation (51)(52)(53)(54).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results about IFN-␣ production from Mtb-infected MDDC are consistent with the data of Cella et al, who found plasmacytoid DC produce type I IFN in mycobacteria-infected lymph nodes (50). It has been also shown that Mtb infection leads to secretion of type I IFN from THP-1 cells (48). All together these observations indicate that the production of IFN type I could play a dual role in Mtb infection by promoting both Th1 and DC differentiation (51)(52)(53)(54).…”
Section: Discussionsupporting
confidence: 93%
“…In fact, IFNs were originally identified as cytokines that mediate antiviral immunity, but were also found to mediate a protective role against bacterial infections (48,49). Our results about IFN-␣ production from Mtb-infected MDDC are consistent with the data of Cella et al, who found plasmacytoid DC produce type I IFN in mycobacteria-infected lymph nodes (50).…”
Section: Discussionsupporting
confidence: 92%
“…Llike LM, Mtb infects and resides in host macrophages. Infection of various cell types with Mtb has been shown to activate NF-κB and IRF-3, and induce expression of both IFNβ and IFNα [117][118][119][120]. A hypervirulent strain of Mtb that induced higher levels of IFNα than another virulent strain, was shown to kill infected mice at a faster rate [120].…”
Section: Type I Ifn Production In Response To Bacterial Infectionmentioning
confidence: 99%
“…IFN␤, the predominant type I IFN induced as part of the innate immune response to viral pathogens in the central nervous system (6), has been shown to inhibit HIV/SIV replication in macrophages (7,8), a major source of productive HIV/SIV replication in the brain (5,9). Transcriptional suppression of the HIV/SIV long terminal repeat (LTR) by IFN␤ involves the induction of a truncated, dominant-negative isoform of the transcription factor CCAAT/enhancer-binding protein ␤ (C/EBP␤), LIP (7,10). There are three known isoforms of C/EBP␤ also referred to as NF-IL6 (nuclear factor-IL6) and LAP (liver-enriched transcriptional activation protein), which are alternatively translated from the same mRNA (11,12).…”
Section: And Simian Immunodeficiency Virus (Siv)-infected Cellsmentioning
confidence: 99%